(untitled) (Development Service Industry Management, 2024)
The article analyzes the peculiarities of the management of universities (including displaced ones) located on the frontline territories, in the conditions of the war between Russia and Ukraine. It has been found that universities in these regions face unique challenges that require adaptation and the development of new management strategies, such as ensuring physical security, psychological support, infrastructure restoration, providing access to communications, quality educational services, hybrid learning models, scientific activities, financing and adaptation to new conditions. It is justified that the research is determined by the need for prompt response to security threats, ensuring the continuity of the educational process, infrastructure restoration, personnel support, international cooperation, development of innovative solutions, and socio-economic stability of the regions. The analysis and systematization of specific aspects of the management of higher education institutions operating in the frontline territories aimed at identifying key challenges and developing effective strategies for overcoming them was carried out. It has been proven that university management includes normative-procedural, structural-functional, and strategic-organizational processes. Peculiarities of the processes of implementation of innovative educational activities and conducting scientific research in universities located in the frontline territories were studied. Synergistic, systemic, statistical, comparative, and functional methods were used for the research. It is found that the synergistic method integrates various management components such as organizational, financial, personnel, and infrastructure management to create a holistic picture of wartime management. The system method allows you to consider the university as a whole system interacting with the environment, using interviews, discussions, surveys, and statistical analysis to collect data. The statistical method evaluates the impact of various factors on university management through quantitative data using means, medians, variances, regression models, and statistical tests. The comparative method analyzes and compares management practices, identifying the best of them to improve efficiency. The functional method assesses the effectiveness of key management functions such as planning, organization, resource allocation, communication, and control. It was found that the methodology for researching the peculiarities of the management of universities in the frontline territories involves a comprehensive approach, which includes the collection of primary and secondary data, qualitative and quantitative analysis, the development of recommendations and their validation, which provides a deep understanding of the problem and the development of effective strategies for the support and development of universities in war conditions.